ANALISA MOTIVASI SISWA DALAM PROSES PEMBELAJARAN BAHASA MANDARIN DI SMP KRISTEN KANAAN PONTIANAK - Marjono, Marjono; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractLearning motivation encourages the inner learning motivation from the students. Its directly encourages the students in learning to get outcomes. It is not only decide how adults learn, but also decide learning behaviour aim effectiveness and the way to choose the learning method. There were some problems during Mandarin class; the students could not read and write Mandarin's words because the students were not interested to Mandarin, and the students don’t have purpose and motivation to learn. That is why it’s important to increase the students motivation in learning of Mandarin. The subject of this research is 7th grade ( 16 students) and 8thgrade ( 15 students) of SMP Kanaan.questionnaire and interview were used in this study. Therefore, increase the learning motivation of our student in Mandarin Class is a very important thing. students become more interested to Mandarin Learning Class. The research results showed that most students have a stronger internal motivation; most students have a stronger external motivation. Keywords: learning Mandarin analysis of motivation